If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 7 + 4x Reorder the terms: -4 + 3x = 7 + 4x Solving -4 + 3x = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 3x + -4x = 7 + 4x + -4x Combine like terms: 3x + -4x = -1x -4 + -1x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -1x = 7 + 0 -4 + -1x = 7 Add '4' to each side of the equation. -4 + 4 + -1x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 7 + 4 -1x = 7 + 4 Combine like terms: 7 + 4 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 0.16-0.02(x+2)=-0.03(1-x) | | r=2*3.14*r | | 0.80=ln(y) | | ln(y)=0.80 | | 16*6d=384 | | 0.8x-5.8=0.6 | | 15x-17=-x+7thenx | | 13b-13/3=2b-5 | | 3+3y=5.5+-4.5y | | a/4-1/4=-3 | | 6y(y+2)-3y+4=6y+y-5 | | -4p-6=-3+4p-7p | | X-y/2=-1 | | 7(2x-3)-7x=0 | | 7-3x=343 | | 0.18(y-7)+0.12y=0.02y-0.7 | | y=12-3/4x-8 | | 2(5w)= | | 0=(-16t^2)+64t+656 | | 6x^2+6y^2=216 | | 5(b-3)=2.5 | | 15x+34=180 | | ((x)(4))-5=y | | 156=x^2+20x | | 447=-8-7n+7 | | 5y+8+3x=180 | | m^3+36= | | 2n+wr=r-7g | | 6x+2y=32 | | 2x^2y^2=0 | | 2(4+3x)=3(x+1)+11 | | -(-1-5)+8=-17+2x |